The Relationship between Patient’s Dental and Oral Health Attitude Towards Patient’s Obedience during Multivisit Treatment - Galih Sampoerno; Rizkina Hendani; Edhie Arif Prasetyo (Conservative Dentistry Journal, 2019)
Background: Caries is the world's number one chronic disease and the prevalence increases in modern times. However, most people ignored and chose dental care when they feel pain. It will worsen the condition of the tooth until require multivisit treatments. The number of visits required for multivisit treatments resulted incomplete treatment due to patient’s non-obedience. One of the factors that affect obedience is attitude. One's attitude towards something will determine someone's behavior towards the same thing. Purpose: To determine the relationship between patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. Method: Analytical observational study with cross-sectional study conducted on 30 patients who came to Conservative Dentistry Unit, Dental Hospital, Faculty of Dental Medicine, UniversitasAirlangga, Surabaya during September-November 2018. The data about the attitude was obtained from questionnaire, while collecting cards of patient’s status and direct interviews of the operators conducted to obtain data about patient’s obedience. Result: Based on the results of Spearman Correlation with α=0,05 obtained p-value=0,364 (p>0,05). It suggests that there was no significant relationship between patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. In addition, test results of the relationship between unexamined variables with obedience obtained p-value=0,010 (motivation), p=0,017 (desire), p=0,004 (perception), and p=0,009 (financing). This suggests that there was a significant relationship between motivation, desires, perceptions, and financing with obedience. Conclusion: There is no relationship between patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. However, other factors found associated, namely motivation, desires, perceptions, and financing.